Experimental Study of a natural ventilation strategy in a Full-Scale Enclosure Under Meteorological Conditions: A Buoyancy-Driven Approach - Austin, Miguel Chen; Bruneau, Denis; Sempey, Alain; Mora, Laurent; Sommier, Alain (KnE Engineering, 2018)
The performance of a natural ventilation strategy, in a full-scale enclosure under meteorological conditions is studied through an experimental study, a buoyancy-driven approach, by means of the estimation of the air exchange rate per hour and ventilation power. A theoretical and an empirical model are proposed based on the airflow theory in buildings and blower-door tests. A preliminary validation, by comparing our results with standards in air leakage rate determination, is made. The experimental study conducted here has shown that the natural ventilation strategy implemented reach promising air exchange rate levels, as they are rather high compared to other experimental studies found in the literature. The proposed models have shown good potential and further analysis should take place. Also, other methods for validating these models should be implemented (for instants: CFD simulation or tracer gas methods), as the one in the standards is rather rough estimations. Keywords: Buoyancy-driven, natural ventilation, ventilation power, blower-door test, airflow in buildings.